Development of an Ethnoscience Electronic Student Worksheet on Buffer Solutions Material to Inculcate Islamic Values - Kamilah, Sofi Nihayatul; Suprihatiningrum, Jamil (Journal of Educational Chemistry (JEC), 2024)
Human actions that exploit natural resources and the environment without limits have caused global conditions to become increasingly concerning. A lack of environmental awareness is also evident in students who neglect to care for and protect the environment, such as by littering. This issue requires serious attention and can be addressed by fostering an environmentally caring character through an integrated ethnoscience approach incorporating Islamic values. Ethnoscience-based learning, integrated with Islamic values, can be facilitated through an electronic student worksheet. This worksheet was designed to help students connect cultural elements with scientific concepts and the teachings of the Quran. Correspondingly, this study developed an electronic student worksheet using a 4D model, encompassing three stages: Define, Design, and Develop. Data from the product development and assessment process were analyzed quantitatively and descriptively. The final product featured character education based on Islamic values. It received an “excellent” rating from material and media experts, while teachers and students responded positively to the media. Overall, this electronic worksheet could potentially improve environmental awareness and instill Islamic values in students.